ENHANCING LEARNING QUALITY: THE ROLE OF INSTRUCTIONAL LEADERSHIP, CLASSROOM MANAGEMENT AND TEACHER PEDAGOGICAL COMPETENCE IN ELEMENTARY SCHOOLS - Puji Rahayu; Titik Haryati; Ghufron Abdullah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to investigate the influence of instructional leadership, classroom management, and teachers’ pedagogical competence on the quality of learning in public elementary schools in Boja District, Kendal Regency. Using a quantitative approach with a correlational survey design, data were collected from 200 elementary school teachers selected through proportionate stratified random sampling. Data were obtained using validated questionnaires and analyzed using multiple linear regression. The findings reveal that all three independent variables have a positive and significant effect on learning quality. Instructional leadership showed the strongest influence (β = 0.487, p < 0.001), followed by classroom management (β = 0.282, p < 0.001), and pedagogical competence (β = 0.151, p < 0.001). The regression model was statistically significant (F = 353.166, p < 0.001), with an adjusted R² of 0.841, indicating that the three variables collectively explain 84.1% of the variance in learning quality. These findings underscore the importance of strengthening school leadership, enhancing classroom management practices, and developing teachers’ pedagogical skills to improve the overall quality of education. This research contributes practical insights for policy formulation and professional development programs aimed at improving learning outcomes in elementary education.